Perjalanan Batin Descartes dan Ignatius Loyola dalam Pencarian Kebenaran: Descartes' and Ignatius' Inner Journey in Search for Truth - Jati, Antonius Siwi Dharma (STF Driyarkara - Diskursus, 2025)
This article examines the interrelation between Descartes’ Méditations métaphysiques (Meditations on First Philosophy) and Ignatius of Loyola’s Spiritual Exercices, with an emphasis on the meditative dimension in the search for truth by the subject engaged in meditation or spiritual exercises. Through a simultaneous and comparative reading using the triplex via framework (via purgativa, via illuminativa, and via unitiva), it asserts that the search for truth is an inner journey, beginning with the purification of the self from disordered attachments, followed by illumination culminating in the discovery of God as the ultimate truth, and finally reaching the union of the self with God. Moreover, it demonstrates that Cartesian philosophy is not merely an intellectual activity but also a spiritual exercise leading to self-transformation and a shift in perspective. Abstrak Artikel ini mengkaji keterkaitan antara Méditations métaphysiques karya Descartes dan Latihan Rohani karya Ignatius Loyola, dengan penekanan khusus pada dimensi meditatif dalam pencarian kebenaran oleh subjek pelaku meditasi atau latihan. Melalui pembacaan simultan dan komparatif menggunakan kerangka triplex via (via purgativa, via illuminativa, dan via unitiva), artikel ini menegaskan bahwa pencarian kebenaran merupakan perjalanan batin yang dimulai dari pemurnian diri dari kelekatan tidak teratur, dilanjutkan dengan pencerahan yang berpuncak pada penemuan Tuhan sebagai kebenaran utama, hingga akhirnya mencapai penyatuan diri dengan Tuhan. Lebih dari itu, artikel ini juga menunjukkan bahwa filsafat Cartesian bukan saja aktivitas intelektual, melainkan sekaligus latihan rohani yang mengarah pada transformasi diri dan perubahan perspektif. Kata-kata kunci: Descartes, Ignatius, meditasi, kebenaran, Res cogitans, Res extensa